Genetic and Chemical Evaluation of Trypanosoma brucei Oleate Desaturase as a Candidate Drug Target - Alloatti, Andrés; Gupta, Shreedhara; Gualdrón-López, Melisa; Igoillo-Esteve, Mariana; Nguewa, Paul A.; Deumer, Gladys; Wallemacq, Pierre; Altabe, Silvia G.; Michels, Paul A. M.; Uttaro, Antonio D. (PLOS ONE, 2010)
Background Trypanosomes can synthesize polyunsaturated fatty acids. Previously, we have shown that they possess stearoyl-CoA desaturase (SCD) and oleate desaturase (OD) to convert stearate (C18) into oleate (C18:1) and linoleate (C18:2), respectively. Here we examine if OD is essential to these parasites. Methodology Cultured procyclic (insect-stage) form (PCF) and bloodstream-form (BSF) Trypanosoma brucei cells were treated with 12- and 13-thiastearic acid (12-TS and 13-TS), inhibitors of OD, and the expression of the enzyme was knocked down by RNA interference. The phenotype of these cells was studied. Principal Findings Growth of PCF T. brucei was totally inhibited by 100 µM of 12-TS and 13-TS, with EC50 values of 40±2 and 30±2 µM, respectively. The BSF was more sensitive, with EC50 values of 7±3 and 2±1 µM, respectively. This growth phenotype was due to the inhibitory effect of thiastearates on OD and, to a lesser extent, on SCD. The enzyme inhibition caused a drop in total unsaturated fatty-acid level of the cells, with a slight increase in oleate but a drastic decrease in linoleate level, most probably affecting membrane fluidity. After knocking down OD expression in PCF, the linoleate content was notably reduced, whereas that of oleate drastically increased, maintaining the total unsaturated fatty-acid level unchanged. Interestingly, the growth phenotype of the RNAi-induced cells was similar to that found for thiastearate-treated trypanosomes, with the former cells growing twofold slower than the latter ones, indicating that the linoleate content itself and not only fluidity could be essential for normal membrane functionality. A similar deleterious effect was found after RNAi in BSF, even with a mere 8% reduction of OD activity, indicating that its full activity is essential. Conclusions/Significance As OD is essential for trypanosomes and is not present in mammalian cells, it is a promising target for chemotherapy of African trypanosomiasis.